'What will the neighbours say?': Legitimacy, Social Control and the Sociocultural Influence of Neighbourhoods in India. (August 2016) - Abraham, Janaki
This article focuses on the everyday practices that make the place of the neighbourhood – social control, legitimacy and support, while also looking at how gender is produced in everyday life in the neighbourhood. In doing this, the discussion underlines the tremendous social and cultural influence of neighbours and the neighbourhood and argues that neighbourhoods need to be seen as a social formation as important as caste, class, ethnicity or religion. This is particularly important given that a strong focus on identities in recent decades has tended to eclipse social formations such as the neighbourhood. This ethnographic discussion is based on fieldwork carried out in neighbourhoods in two towns in India, Thalassery in Kerala, South India and Bikaner in Rajasthan, North India.